PLDT monopoly break its effect on subscribers in Iloilo City - Baylon, Marilou T.; Gallo, Nieva Jean C.; Mucho, Scarlet P.; Quicot, Rosalie C.; Ragodo, Alovette S. (1998.)
This study was carried out to determine the effects of the PLDT Monopoly break on subscribers of Iloilo City specifically, it aired to find out if the services of PLDT had improved, if the emergence of other telecom companies provide better services and it has contributed to the growth of business in Iloilo City. This study was undertaken by identifying three groups of respondents namely, the PLDT Household Subscribers, non PLDT household subscribers and PLDT businessmen subscribers. Three sets of questionnaires were given out to the said respondents. Interviews were also conducted to gain more information about the telecom companies and the services that they provide. The results of the study showed that PLDT's services have improved, other telecom companies provide better service and it contributed to the growth of businesses in the city.
Research Paper (BA 200 - Business Research). -- [Iloilo City] : University of the Philippines in the Visayas-College of Management, March 25, 1998.